Perception on Acceptability of Nigerian Females on Beaded Jewellery Empowerment for Entrepreneurial Development - Taibat Tunrayo Adebisi; Oluwafeyikemi Edith Bashorun; Shakirat Odunayo Abdulkadir; Banke Adebola Adepoju (Journal of Consumer Sciences, 2021)
The study investigates the perception of acceptability of Nigerian females on beaded jewellery empowerment for entrepreneurial development. Four research questions with two null hypotheses were formulated and tested. Descriptive research of a survey type was adopted. 70 female students from fine and applied arts and 70 female adults from Ilorin metropolis, Nigeria were used. Proportional sampling technique was used to select the 140 participants. A self-structured questionnaire with six sections was used to seek information from them. Data collected were analyzed using frequency and percentage while the hypotheses were tested using chi-square at 0.05 level of significance. Based on the findings, the participants perceived that: beads are the major materials used, the skill might occupy a female’s time and generate income. Profits realized can be substantial for the producers and sellers. The six self -samples were accepted based on colour, design, texture and shape. It can be concluded that the skill might be acquired, used to curb female idleness and unemployment. Among the recommendations stated are: bead crafts should be included in the curriculum at all levels of study, and more aware of its acceptance on mass media and fashion shows for love of beads concerning culture, value and significance.